Tensile and fatigue properties of unidirectional kenaf fibre reinforced epoxy composites - Abdullah, Abdul Hakim (2011)
This research work is concerned with the tensile and fatigue properties of unidirectional kenaf fibre reinforced epoxy composites at three different fibre volume fractions; 0%, 15% and 45%. Two types of composites material, namely kenaf/epoxy A composites and kenaf/epoxy B composites were used. The chemical functions of epoxy A and epoxy B were examined by using Fourier transform infrared technique from 500-4000 cm-1 frequency band. The composites were prepared using hand lay-up technique. The tensile tests were performed in accordance to ASTM D-3039 while fatigue tests in accordance to ASTM D-3479. All fatigue tests were conducted at constant stress amplitude, frequency of 5 Hz and the maximum stress applied was between 90-40% of ultimate tensile stress. The analysis of surface morphology was done by using scanning electron microscope. The results showed that the tensile properties improved as the fibre volume fraction increased. Although the stress-strain curves of 15% and 45% fibre volume fraction composites did not exhibit any yield points, the bi-linear expression that transition region behaviour was observed. On the other hand, the elastic modulus decreased drastically after passing over this region but the composites remained as brittle material. Using T-test, the transition point had been statistically proven different for 15% and 45% kenaf/epoxy composites. The Fourier transforms infrared spectra showed that similar chemical functional group present in epoxy A and B which indicated the bi-linear expression was contributed by matrix. Similar to those tensile properties, the effect of fibre volume fraction in composites resulted better fatigue life and fatigue resistance. However, there was no indication of endurance limit characteristic had been shown by composites in S-N curves. The survived 1 million cycle specimens was apparently within or below the transition region and the damages received in this region were ultimately greater. Statistical analysis using Weibull distributions confirmed the failure was caused by fatigue failure. The beginning of damages was matrix cracking and eventually, the reason of the transition region behaviour in stress-strain curves.